Isozyme variation in the southern green stink bug Nezara viridula (L.) (Heteroptera: Pentatomidae) - Meglič, Vladimir (Acta entomologica slovenica (Ljubljana), 2002)
The southern green stink bug Nezara viridula (Heteroptera; Pentatomidae) is a cosmopolitan species with a still uncertain geographical origin. The ancestralhome of this species is supposed to be Africa and/or the Mediterraneanč presumably it was spread world-wide during the last two centuries by human trade and agriculture. Bugs found today on different continents do not differ morphologically, however there are substantial differences in their mating behaviour. We used horizontal starch gel electrophoresis to determine the suitability of biochemical markers for assessment of genetic variation between geographically isolated populations ofN. viridula. The initial survey of populations from Slovenia, France, FrenchWest Indies, and Brazil resulted in the resolution of polymorphic banding patterns within the following enzyme systemsČ glucosephosphate isomerase (GPI), isocitrate dehydrogenase (IDH) malate dehydrogenase (MDH), malic enzyme (ME), mannosephosphate isomerase (MPI) and phosphoglucomutase (PGM). Results indicate that in some enzyme systems such as PGM and MPI there are consistent differences among the tested populations.
Keywords: biokemija; genska raznolikost; izoencimi; stenice; zoogeografija